Organizational identification and “intrapreneurial” behavior - Moriano, Juan Antonio; Topa, Gabriela; Valero, Encarna; Lévy, Jean-Pierre (Anales de Psicología / Annals of Psychology, 2009)
This study aims to analyse the influence of Organizational Identification on employees’ “Intrapreneurial” Behavior (IB). For this purpose, we tested a psychosocial model which explains the influence of organizational factors (management support, work discretion, rewards, time availability and task uncertainty) on IB through the mediation of organizational identification. The sample consists of 618 employees from several governmental and private organizations. They filled out an anony-mous questionnaire. Structural Equation Modeling (SEM) was used to ana-lyze the data. The results confirm the validity of the model proposed and the role of organizational identification as a mediator variable of organizational factors’ effects. Therefore, if a person identifies him or her self with the organization where he or she works, it is more likely that he or she takes risks and pursues innovative actions that will be to the advantage of the whole organization.